Functional Pediococcus acidilactici BC1 for the revitalization of ethnic black carrot kanji of indian subcontinent. (January 2021) - Manzoor, Mehak; Sharma, Vikrant; Singh, Deepti; Sohal, Jagdip Singh; Aseri, Gajender Kumar; Khare, Neeraj; Vij, Shilpa; Saroop, Jyoti; Sharma, Deepansh
Abstract: The present study aimed to screen the autochthonous lactic acid bacteria (LAB) to produce the black carrot (BC) Kanji, a Lacto-fermented beverage consumed in the Indian sub-continent. But the production of Kanji has never been commercialized using mono or mixed strain. Autochthonous P. acidilactici BC1 has been isolated from the spontaneously fermented Kanji. Subsequently, pasteurized BC juice was inoculated with 10 % (v/v) pre-culture with 2% (w/v) added sugars viz. brown sugar, glucose, and jaggery respectively. The effect of salt concentration (1–10 % w/v) and varying pH range (1.0–8.0) has been evaluated on the growth of P. acidilactici BC1. During fermentation, pH, titratable acidity (TA), LAB count, and total suspended solids (TSS) were observed and recorded at regular intervals. The pH of the BC juice decreased from an initial value of 5.12 to 3.27, 8.0–11.5 g/L lactic acid was accumulated after completion of the fermentation on the 9 th day. The LAB count has reached a maximum count of 8.92 log CFU/mL during the fermentation. Total phenolics and antioxidant activity has been increased during and after fermentation i.e. 37.19 % and 45.70 % respectively. Probiotic traits of the P. acidilactici BC1 is an added benefit to the consumer and can be consumed as a product to be probiotic in nature. It was established that the fermentation of BC juice with added brown sugar and jaggery comes out as most accepted in all the variants due to the enrichment in phenolics, antioxidants, and probiotic properties. The protective nature of the fermented BC juice to control Salmonella enterica and Shigella boydii is a striking functionality of the fermented beverage. Controlled fermentation with plant phytochemicals and probiotic attributes can be explored as a potential food matrix loaded with antioxidants and postbiotics. Highlights: Isolation of autochthonous starter culture Pediococcus acidilactici BC1 for Kanji fermentation. Functional & probiotic traits showed by starter culture. Optimization of the fermentation process and sensory analysis. Pre-technological process development for uniform quality and taste of the beverage.